Identification of unsteady aerodynamic loads using aeroelastic response and orthogonal functions - Marqui, C. R.; Bueno, D. D.; Goes, L. C.S.; Gonçalves, P. J.P. [UNESP] (My University, 2012)
The objective of this paper is the identification of aerodynamic parameters by the use of aeroelastic response using orthogonal functions. The unsteady aerodynamic forces acting on an aeroelastic system can calculated in the subsonic regime by use of the doublet lattice method, for example, providing a model in frequency domain that needs to be coupled structural dynamics. To obtain a time domain representation of the aeroelastic system, rational functions approximation can be used to represent aerodynamic forces. The most common methods found in literature to approximate these unsteady generalized forces from the frequency to time domain are the least square (LS), matrix Padé, and minimum state. In this context, this work proposes the use of orthogonal functions to represent the aeroelastic output from a state space representation of the system. These functions are easily integrated by using a so-called operational matrix of integration. Consequently, it is possible to transform the aeroelastic equations of motion into algebraic equations. After mathematical manipulation the unknown aerodynamic parameters are determined. Numerical simulations, involving a typical section (three degree-of-freedom) aeroelastic system are used to help illustrate the method that could be applied in an identification experiment. © (2012) by the Katholieke Universiteit Leuven Department of Mechanical Engineering All rights reserved.